PENERAPAN LEAN DISTRIBUTION UNTUK MEMINIMALISIR WASTE PROSES PENGIRIMAN BARANG PADA PT XYZ: Lean Distribution PT XYZ - Shinta Nurlita; Imas Chandra Pratiwi; Titik Purwinarti (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2026)
The current goods delivery process at PT XYZ still faces issues such as delivery delays. This is due to the presence of non-value-added activities in the goods delivery process. The objective of this study is to reduce waste and improve efficiency in the distribution process at PT XYZ. Therefore, the researcher conducted an investigation by mapping the actual goods delivery flow using one of the Lean tools, namely VSM. Next, the researcher identified the waste occurring using the WAM tool, resulting in the dominant waste being transportation waste at 18.11% and waiting waste at 17.38%. The WAM results were further analyzed using VALSAT, with the highest total being the PAM tools. Therefore, improvement proposals to minimize these wastes include relocating the cross-docking warehouse, digitizing the goods inspection process, and creating Standard Operating Procedures (SOPs). As a result, the research yielded a VA value of 1,712.65 seconds, an NVA value of 116.67 seconds, and an NNVA value of 2,412.89 seconds. This reduces the future state map of the goods delivery process by 22% from 5,459.91 seconds to 4,242.21 seconds and reduces the lead time for goods delivery from 5 days to 4 days.